ANALISIS KESIAPSIAGAAN RUMAH SAKIT DALAM UPAYA PENANGGULANGAN BENCANA KEBAKARANDI RSKD DADI PROV SUL-SEL - Nurmulia Wunaini; Ranti Elva Rahmalia (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2022)
Countermeasures disaster are a series of efforts to establish development policies that may pose a risk of disaster, disaster prevention activities, emergency response, and rehabilitation. The hospital is one of the workplaces that can be at risk of a fire. The Dadi Hospital of South Sulawesi Province experienced fire incidents in 2015 and 2016 due to cigarette butts and an electric short circuit.The purpose of this study is to analyze hospital preparedness in an effort to deal with fire disasters at Dadi Hospital, South Sulawesi Province. The research design used in this study is qualitative, where researchers want to describe in-depth information from informants regarding the analysis of hospital preparedness in fire disaster management efforts at Dadi Hospital in South Sulawesi Province through in-depth interviews and secondary data observations.The results of this study found that the hospital has management related to fire prevention such as the availability of active protection such as APAR, Spinkler, Heat Detector, Smoke Control System, Alarm and passive protection such as emergency stairs, emergency exits, gathering points, evacuation routes as well as testing and fire protection check.